Intimate partner violence and early interruption of exclusive breastfeeding in the first three months of life - Maria Helena Hasselmann; Ana Cristina Lindsay; Pamela J. Surkan; Gabriela Vasconcellos de Barros Vianna; Guilherme L. Werneck
Abstract: The aim of this study was to investigate the role of intimate partner violence in the early interruption of exclusive breastfeeding in the first three months of life. We used data from a prospective cohort of 564 children attending four primary health clinics in Rio de Janeiro, Brazil. Interruption of exclusive breastfeeding was defined as a child receiving any kind of liquid or solid, regardless of breast milk intake, measured by a 24 hour recall. The Portuguese version of the Conflict Tactics Scales (CTS-1) was used to assess intimate partner violence. Associations were expressed as prevalence ratios and relative risks and their respective 95% confidence intervals. Children of mothers who experienced severe violence had 30% greater likelihood of early interruption of exclusive breastfeeding in the second month of life as compared to those who did not experience this type of violence. Strategies in health services for promoting exclusive breastfeeding should consider identifying and addressing family violence.